IMPACT OF FINANCIAL INCLUSION, GOVERNMENT EXPENDITURES IN EDUCATION AND HEALTH SECTORS ON HUMAN DEVELOPMENT IN INDONESIA - Simatupang, Mulia (Journal of Economic Development, Environment and People, 2020)
ABSTRACT The purpose of this paper in to assess the impact of financial inclusion and government expenditures in education and health sectors in order to increase human development index. Government expenditures has important role to support economic growth and welfare for its people. Fiscal policy expenditures in education and health sectors are kind of significant government policy to increase human development. It is believed that financial inclusion has also important role to reduce poverty and indirectly increase human development index. Financial inclusion has positive impacts to human development index component along with government expenditures in education and health sector. In the years ahead, The Government should prioritize and increase budget in order to increase human resources quality in Indonesia.